Cradle to kindergarten : a new plan to combat inequality - Chaudry, Ajay (Russell Sage Foundation, 2017)
Early care and education for many children in the United States is in crisis. The period between birth and kindergarten is a critical time for child development, and socioeconomic disparities that begin early in children's lives contribute to starkly different long-term outcomes for adults. Yet, compared to other advanced economies, high-quality child care and preschool in the United States are scarce and prohibitively expensive for many middle-class and most disadvantaged families. To what extent can early-life interventions provide these children with the opportunities that their affluent peers enjoy and contribute to reduced social inequality in the long term? Cradle to Kindergarten offers a comprehensive, evidence-based strategy that diagnoses the obstacles to accessible early education and charts a path to opportunity for all children. --